Reduced Prenatal Pulmonary Lymphatic Function Is Observed in Clp1K/K Embryos With Impaired Motor Functions Including Fetal Breathing Movements in Preparation of the Developing Lung for Inflation at Birth - Szoták-Ajtay, Kitti; Szõke, Dániel; Kovács, Gábor; Andréka, Judit; Brenner, Gábor B.; Giricz, Zoltán; Penninger, Josef; Kahn, Mark L.; Jakus, Zoltán (Frontiers in Bioengineering and Biotechnology, 2020)
Embryonic lungs must be inflated immediately after birth to establish respiration. In addition to pulmonary surfactant, recently, we have revealed lymphatic function as a previously unknown regulator of prenatal lung compliance that prepares the embryonic lung for inflation at birth. It is well-documented that the late gestation embryo performs episodic breathing-like movements called as fetal breathing movements (FBMs), but the physiological importance of these events is not clear. Here we aimed to study the physiological role of FBMs in preparation for air inflation at birth. Clp1K/K late gestation embryos develop a progressive loss of spinal motor neurons associated with axonal degeneration and denervation of neuromuscular junctions serving as an ideal genetic model to test the possible role of FBMs. We demonstrated that Clp1K/K newborns show impaired motor function resulting in fatal respiratory failure after birth. Next, we showed that the alveolar septa are thicker, and the alveolar area is reduced in Clp1K/K late gestation embryos, while the expression of molecular markers of lung development are not affected. Importantly, pulmonary lymphatic vessels are dilated and the prenatal pulmonary lymphatic function is reduced in Clp1K/K late gestation embryos. Our results have revealed that Clp1K/K mice show impaired motor functions including FBMs, and late gestation Clp1K/K embryos display reduced prenatal lymphatic function and impaired lung expansion represented as thickened alveolar septa and reduced alveolar area in preparation of the developing lung for inflation at birth. These findings suggest a possible mechanism that FBMs, similarly to breathing movements after birth, stimulate prenatal lymphatic function in pulmonary collecting lymphatics lacking smooth muscle coverage to prepare the developing lung for inflation and gas exchange at birth. Moreover, these results raise the possibility that stimulating FBMs during late gestation might be an effective way to reduce the risk of the development of neonatal respiratory failure.